CHATGPT AND AI TOOLS IN THE CLASSROOM: HOW TO INTEGRATE WITHOUT REPLACING CRITICAL THINKING (REMUNOM, 2026)
The rapid advancement of artificial intelligence (AI)-based technologies, such as ChatGPT, has significantly reshaped educational environments, raising urgent debates regarding their pedagogical integration. This article aims to critically examine both the potential and the risks of using generative AI tools in classroom settings, particularly in terms of preserving and fostering critical thinking among students. Although these technologies offer numerous possibilities for personalized learning, task automation, and broader access to knowledge, there is growing concern about their uncritical application, which may jeopardize the development of intellectual autonomy, ethical reflection, and creativity. Drawing on a comprehensive literature review that includes authors such as Selwyn (2021), Williamson (2022), Luckin (2023), Holmes (2021), Zawacki-Richter (2020), Knox (2023), Perrotta (2024), and Wang (2025), the article discusses the essential role of teachers in mediating the use of such tools and in designing pedagogical strategies that emphasize authorship, inquiry, and reflective judgment. It is argued that the mere adoption of AI tools without a critical and formative intentionality can result in technological dependency, dilute the educational value of writing, and constrain cognitive diversity. Therefore, it is advocated that AI be incorporated into pedagogical practices as an ally in the construction of meaningful learning, if it is anchored in ethical, critical, and democratic principles. Finally, the article points out directions for future research and suggests the development of public policies, ongoing teacher training, and updated curricula that promote a critical and conscious digital education.